PROBLEMS OF ENERGY EFFICIENCY IN UKRAINE AND INTERNATIONAL EXPERIENCE OF IMPLEMENTATION OF ENERGY EFFICIENCY IN EU COUNTRIES - CHEREP, Oleksandr; OSMAKOVSKA, Ksenia; LYSHCHENKO, Olena; BOYKO, Ostap (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article is devoted to the issue of energy efficiency in Ukraine and the international experience of implementing energy efficiency in the countries of the European Union. In the context of growing problems related to the reduction of energy consumption and the use of renewable energy sources, attention to energy efficiency issues is becoming more and more relevant. The issue of energy efficiency in Ukraine is considered, attention is focused on insufficient awareness and education of the population, insufficient funding and limited access to resources, and the international experience of implementing energy efficiency in EU countries is considered as a potential solution for solving energy efficiency problems in Ukraine. The article will analyze EU legislation and programs aimed at stimulating energy efficiency, as well as highlight successful practices and initiatives that contribute to energy-efficient development. Special attention is paid to ways of implementing energy efficiency in EU countries, in particular, the use of energy-efficient technologies in construction and reconstruction, stimulation of the use of renewable energy sources, implementation of energy-efficient heating and cooling systems, as well as financing mechanisms for energy efficiency projects. The current state of energy efficiency in Ukraine is analyzed, including the main challenges and obstacles the country faces. Special attention is paid to the legislative and regulatory framework governing energy efficiency in Ukraine, as well as existing programs and initiatives. Attention is focused on the international experience of implementing energy efficiency in the EU countries.